Measures of Social Assistance to the Population of the Yenisei Province Taken by Anti-Bolshevist Governments (June 1918 — December 1919) - Kattsina, Tatyana A.; Mezit, Ludmila E. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2018)
Referring to the materials of the uyezd political newspapers Narodny Vestnik, Yeniseysky Vestnik, documents first found in the State Archives of the Russian Federation, and the State Archives of Krasnoyarsk Krai, this article considers a little-studied issue of social history, i.e. the ways in which the principles and mechanisms of implementation of social assistance to the underprivileged groups of the population were formed in the emergency conditions of the Civil War. The analysis is limited to the territory of the Yenisei Province. Referring to it, it is possible to form an idea of how the processes in question took place in the life of such large regions as the Urals, Siberia, and the Far East. The chronological framework of the article includes the period of the Provisional Siberian Government (June-November 1918) and the Russian government of the Supreme Governor Admiral Kolchak (November 18, 1918 — December 1919), which considered the Siberian outskirts a “rescue territory” for the future democratic non-Soviet state. In order to achieve a holistic perception of social assistance practices and provide a basis for further in-depth study in this field, it is essential to determine the main trends of the state policy and the experience of local authorities in the field of social assistance in terms of continuity, interaction of its actors, and the conformity of the results with social expectations. For the purposes of the study, the authors use general research methods and methods of general historical and concrete historical research, the synthesis of the formational, historical-anthropological and activity approaches, and the theory of modernisation. The authors conclude that successful cooperation during the period under review proved impossible for a number of reasons: the lack of financial resources of the anti-Bolshevik governments, the instability of the political and military situation in the region, the absence of specialists in the government who had experience in managing social policy. Neither the Provisional Siberian Government nor the Russian government of the Supreme Governor Admiral Kolchak managed to review the number of socially underprivileged categories of the population, the state did not provide financial support to private and public charitable organisations, the decisions taken were not executed because of an ill-conceived implementation mechanism. The compromise solutions offered by the anti-Bolshevist governments could not satisfy the participants of social relations, which led to the collapse of the government’s social cooperation programme.